(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2021)
We report two critically ill children (aged 5–8 years), presented with features of multisystem inflammatory syndrome in children (MIS-C) from January 1 to February 2, 2021 at a tertiary-care center (Combined Military Hospital) in Dhaka, Bangladesh. Both of the previously healthy children tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections. Clinical presentations were similar in both with fever, gastrointestinal complaints, respiratory distress, rash, headache and myalgia. Laboratory values were high levels of C-reactive protein, D-dimers, B-type natriuretic peptide (Pro-BNP), troponin I and low albumin levels in both patients. Evaluations for other infectious diseases werenegative. Both the patients were critically ill, requiring admission to the pediatric intensive care unit (P-ICU) due to circulatory shock and needed inotropes. One of the patients had respiratory failure and required mechanical ventilation. Both patients received steroids, Intravenous Immunoglobulin (IVIG), Remdesivir, Tocilizumab. MIS-C is a recently recognized pediatric illness spectrum in association with SARS-CoV-2 infection. As for manifestations of COVID-19 infection and its consequences in children is myriad and knowledge about MIS-C is evolving, reporting is essential for better understanding of clinical clues of MIS-C and finding out a panacea through experience sharing. JAFMC Bangladesh. Vol 15, No 1 (June) 2020: 76-79